Teaching of Electromagnetics Theory at Kolej Universiti Teknikal Kebangsaan Malaysia - Md Ghazaly, Mariam; Gan, Chin Kim (2005)
Electromagnetics (EM) theory is considered as one of the most fundamental subjects for electrical engineering students. With rapid technological development, universities face the pressure of covering the up-to-date engineering materials in four years. Many universities have squeezed the curriculum of EM theory into one semester. The challenge arises on how to deliver this subject effectively in this limited amount of time. This paper descnbes the Practice and Application-Oriented (PAO) approach used by the Faculty of Electrical Engineering, KUTKM in conveying EM theory efficiently to the students.